Experimental Investigation into the Effects of Fracturing Fluid-Shale Interaction on Pore Structure and Wettability - Yan Zhang; Zhiping Li; Fengpeng Lai; Hao Wu; Gangtao Mao; Caspar Daniel Adenutsi (Geofluids)
One of the main techniques for the exploitation of shale oil and gas is hydraulic fracturing, and the fracturing fluid (slick water) may interact with minerals during the fracturing process, which has a significant effect on the shale pore structure. In this study, the pore structure and fluid distribution of shale samples were analyzed by utilizing low-pressure liquid nitrogen adsorption (LP-N2GA) and nuclear magnetic resonance (NMR). The fractal analysis showed that the pore structure of the sample was strongly heterogeneous. It was also found that the effect of slick water on pore structure can be attributed to two phenomena: the swelling of clay minerals and the dissolution of carbonate minerals. The swelling and dissolution of minerals can exist at the same time, and the strength of them at different soaking times is different, leading to the changes in specific surface area and pore size. After the samples were soaked in the slick water for two days, the contact angle reached the minimum value (below 8°), which means the sample is strongly hydrophilic; then the contact angle increased to above 38° with longer soaking times. The connected pore space in the shale matrix is enlarged by the soaking processing. Therefore, an in-depth understanding of the interaction between the fracking fluid and shale is essential to deepen our understanding of changes in the pore structure in the reservoir and the long-term productivity of shale gas.